The degree of project manager's project system compliance and project performance in Eskom distribution asset creation project execution department in the Limpopo Operating Unit - Baloyi, Maggy Tlakale (University of Limpopo, 2016)
Project systems allow project managers to carry out work in a professional and well organised manner. These systems are created and maintained to advance project performance. Eskom spends a lot of resources on the creation and maintenance of project systems. The literature on project systems shows that, in spite of advancement in project managements processes, systems and tools, project success has not significantly improved. This problem raises questions about the value and effectiveness of project systems. Therefore this paper reports about the correlation between the degree of project manager’s compliance to project systems and project performance in Eskom Distribution Limpopo Operating Unit. The study looked at the performance of 10 projects and used empirical data on designers, planners, managers and project managers working in Eskom Distribution LOU to measure the compliance level of employees to project systems when carrying out the 10 chosen projects or any other projects not listed. A total of 45 completed questionnaires were analysed. Correlation analysis tests found a negative correlation between project manager’s project systems compliance level and project performance in terms of schedule and cost. The conclusion found was that as the compliance level on project systems increases, project performance decreases. Meaning there is an inversely proportional relationship between project system compliance level and project performance. Additionally, a lower level of knowledge than expected on the project managers, designers, and planners was found. Keywords: Project performance, Project systems, Correlation, Adherence,
Thesis (MBA.) -- University of Limpopo, 2016
Keywords: Project performance; Project systems; Correlation; Adherence; Project alert; Coefficient of concordance